When and how to treat women with HER2-positive, small (pT1a-b), node-negative breast cancer?. (August 2018) - Gori, Stefania; Turazza, Monica; Modena, Alessandra; Duranti, Simona; Zamboni, Giuseppe; Alongi, Filippo; Carbognin, Giovanni; Massocco, Alberto; Salgarello, Matteo; Inno, Alessandro
Highlights: pT1a-b pN0 breast cancer generally has an excellent prognosis but HER2+ve status is associated with decreased survival. To date, there are no definitive specific treatment guidelines on HER2+ve, pT1a-b, pN0 breast cancer. We summarize the current data available on prognosis and treatment of these breast cancer. Treatment choice should be made balancing absolute benefit and risk of toxicity. Abstract: Small (pT1a-b), node-negative (pN0) breast cancer generally has a good prognosis. However, HER2-positive status is associated with an increased risk of relapse and decreased survival even in these tumors. Although there are only few data from prospective randomized trials, results of retrospective studies suggest adjuvant chemotherapy plus trastuzumab may improve outcomes of patients with pT1a-b pN0 HER2-positive breast cancer. On the other hand, trastuzumab is potentially associated with increased cardiac toxicity, especially when combined with anthracycline-based chemotherapy. A valid strategy for improving cardiac safety is the addition of trastuzumab to non-anthracycline chemotherapy, whereas a shorter duration of trastuzumab should be not routinely considered although might represent an option for selected patients at low risk of relapse and very high risk of cardiac events. Therefore, the choice of adjuvant treatment for patients with pT1a-b pN0 HER2-positive breast cancer should be done on individual basis, carefully weighing benefits and risks.